SYSTEMIC DEPENDENCES OF CHANGES IN BODY COMPOSITION WITH THE PROGRESSION OF NON-COMMUNICABLE DISEASES - Nevoit, G.V.; Potiazhenko, М.М.; Mintser, О.P. (World of Medicine and Biology, 2021)
The article covers practical issues of assessing the clinical significance of the use of instrumental impedancemetry to determine body composition as an objective reflection of the consequences of the lifestyle of patients. The purpose of the study is to determine the clinical and pathogenic features of Non-communicable Diseases based on the results of instrumental impedancemetry and to improve approaches to the management of patients with non-communicable diseases in the first and second stages of therapeutic care. The article presents the results of instrumental impedancemetry of body composition of functionally healthy people of different levels of physical fitness and patients with non-communicable diseases, which were distributed depending on the level of comorbidity and the stage of the cardiovascular continuum. Based on the assessment of impedancemetry parameters, conclusions were made about the presence of systemic dependences of body composition in the progression of Non-communicable Diseases, the significant clinical significance of instrumental impedancemetry in the examination of patients was established, and the percentage of non-communicable diseases.
Keywords: non-communicable diseases; objective structured clinical examination; impedance body composition; obesity; muscle percentage